Assessing the influence of microclimate and vegetation structure on hymenoptera diversity and abundance - Azlan, Nurul Iffah Nadhirah (2019)
Hymenoptera is beneficial for ecosystem services such as natural predation and pollination. Due to high demand in agriculture, massive forest land has been converted into monoculture plantations affecting Hymenoptera assemblages. Moreover, different habitat quality characteristics due to land use changes influence Hymenoptera biodiversity. Thus, this study was conducted to determine Hymenoptera diversity and abundance in different habitat landscapes between polyculture (orchard) and monoculture system (oil palm and rubber plantation) and to investigate the influence of microclimate condition and vegetation structure on Hymenoptera assemblages. This study was conducted at Kampung Ulu Sepri, Kampung Empang Batu and Kampung Batang Sepri located in Pedas, Negeri Sembilan. Hymenoptera sampling was carried out using yellow pan trap in 30 sampling points with 100 meters distance between points in each plantation area (a total of 90 sampling points). Environmental data was collected vegetation structure and microclimate was collected during solar noon. Overall, 440 Hymenoptera individuals belonging to 7 families (Vespidae, Sphecidae, Crabonidae, Megachilidae, Pompilidae, Braconidae and Ichneumonidae) were collected. Hymenoptera family and abundance were higher in rubber plantations (7 family, 232 individuals) compared to oil palm plantations (6 family, 44 individuals) and orchards (5 family, 164 individuals). Hymenoptera family were dominated by Ichneumonidae in rubber plantations and orchards, whereas oil palm dominated by Braconidae family. These result provide clear evidence that landscapes surrounding rubber plantation with high vegetation structure affects the abundance and number of Hymenoptera family. Hence, vegetation structure plays an important role to maintain social bees and wasps abundance.